Research on digital empowerment, innovation vitality and manufacturing supply chain resilience mechanism - Huiyan Wang; You Chen; Jiaping Xie; Caixuan Liu (PLoS ONE, 2025)
As global manufacturing competition increasingly emphasizes supply chain resilience, enhancing the risk resistance of manufacturing supply chains through digital empowerment has become a critical priority. This study leverages the opportunities of the digital economy to deeply investigate the mechanisms that enhance supply chain resilience. Using data from China’ s A-share listed manufacturing companies from 2012 to 2020, a research framework is constructed based on information asymmetry and transaction cost theories. Employing text analysis and factor analysis, the study develops indicators for digital empowerment and supply chain resilience and examines their relationship through both theoretical analysis and empirical testing. The findings reveal that: (a) Digital empowerment significantly enhances supply chain resilience in the manufacturing sector, and this conclusion is robust across various robustness checks. (b) Mechanism analysis demonstrates that digital empowerment drives supply chain resilience primarily by enhancing innovation vitality within enterprises. (c) The moderating analysis shows that environmental uncertainty positively influences the resilience of digitally empowered manufacturing supply chains. (d) Further analysis indicates that the effects of digital empowerment on supply chain resilience vary depending on factor intensity, supply chain position, and industry competition levels. These results validate the positive role of digital empowerment in promoting supply chain resilience and explore the ’black box’ mechanism from the perspective of innovation vitality. The study also highlights the moderating influence of environmental uncertainty. By advancing the understanding of how the digital economy fosters high-quality development in manufacturing, this research provides actionable insights for strengthening supply chain resilience, achieving greater control over supply chain dynamics, and promoting deeper integration between digital technologies and the real economy.